Calendar Degradation Mechanism of Lithium Ion Batteries with a LiMn2O4 and LiNi0.5Co0.2Mn0.3O2 Blended Cathode. (4th January 2017) - Ando, Keisuke; Matsuda, Tomoyuki; Myojin, Masao; Imamura, Daichi
Abstract : In this study, we conducted systematic storage life tests using commercial 18650-type lithium-ion batteries with Li1− x Mn2 O4 - and Li1− y Ni0.5 Co0.2 Mn0.3 O2 -blended cathodes at four temperatures (0°C, 25°C, 45°C, and 60°C) and six state of charges (SOCs) (0%, 40%, 60%, 70%, 80%, and 100%). We conducted a non-disassemble dV/dQ curve analysis to understand the cell-degradation mechanism. Cathode/anode reaction region slips mainly caused cell capacity fading and were accelerated by temperature and SOC. Cathode degradation was also observed at specific SOCs of 60% and 70% at 45°C and 60°C. The proposed method calculated the Li composition of Li1− x Mn2 O4 from the dV/dQ curve and the cell charge capacity on adjusting the SOC value. The Li composition obtained was such that manganese from Li1− x Mn2 O4 was easily eluted at SOCs of 60% and 70%. Even at fixed SOC definition voltages, the Li compositions were observed to vary as degradation proceeded; this variation affected the degradation rate.